Beyond the blonde - Flynn-Hui, Kathleen (New York : Warner Books, 2005)
' A young woman from rural New Hampshire is thrust into the world of New York's hottest hair salon, tending to socialites and actresses, models and moguls'-- Provided by publisher
Keywords: Young women -- Fiction; Beauty operators -- Fiction; New York (N. Y.) -- Fiction; Bildungsromans